A colorimetric sensing platform based upon recognizing hybridization chain reaction products with oligonucleotide modified gold nanoparticles through triplex formation. Issue 5 (20th January 2017) - Zou, Li; Li, Ruimin; Zhang, Manjun; Luo, Yanwei; Zhou, Nian; Wang, Jing; Ling, Liansheng
Abstract : A colorimetric sensor was developed based upon recognition of HCR products with TFO modified AuNPs through triplex formation. Abstract : A novel colorimetric sensing strategy for biomolecule assay has been developed, which integrates the signal amplification of the hybridization chain reaction (HCR) with the assembly of gold nanoparticles (AuNPs) through triplex formation. In the presence of targets, the HCR process can be triggered, the HCR products are specifically recognized by triplex-forming oligonucleotide (TFO) functionalized AuNPs, accompanying the aggregation of AuNPs and a dramatic absorbance change at 522 nm. In addition, the DNA hairpin probes can form rigid triplex structures with TFO-functionalized AuNPs in the absence of targets, resulting in a negligible background signal. By taking advantage of this new biosensor platform, a broad range of targets, involving nucleic acids, small molecules and proteins, have been successfully determined with high sensitivity and selectivity, which may hold great potential for practical application.